2015
DOI: 10.1007/s12350-015-0143-2
|View full text |Cite
|
Sign up to set email alerts
|

Cut-off values of myocardial perfusion gated-SPECT phase analysis parameters of normal subjects, and conduction and mechanical cardiac diseases

Abstract: In this pilot study, different CO values of phase histogram parameters were observed between normal subjects and patients with conduction and MCD, and between patients with and without criteria of cardiac resynchronization therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 30 publications
1
14
0
2
Order By: Relevance
“…Romeo-Farina reported that both bandwidth and phase SD showed excellent ROC AUCs, and these indices were the most important parameters [26]. ROC AUCs of bandwidth, phase SD, and entropy showed good diagnostic accuracy with values ≥0.850 in our results.…”
Section: Discussionsupporting
confidence: 67%
“…Romeo-Farina reported that both bandwidth and phase SD showed excellent ROC AUCs, and these indices were the most important parameters [26]. ROC AUCs of bandwidth, phase SD, and entropy showed good diagnostic accuracy with values ≥0.850 in our results.…”
Section: Discussionsupporting
confidence: 67%
“…12 While there are expected differences in phase analysis indices when GSPECT data are reconstructed by different software, 13,14 the normal cut-off used by Fudim et al 4 are strikingly higher than those reported previously in similarly large derivation cohorts. 15 These values are significantly higher than reported from the same software (likely older version) by Chen et al (initial work on LVD) 12 and by Romero-Farina et al, 15 among normal controls. If this severe variability in measures of phase analysis is solely due to change in SPECT software versions need further investigation, as this will significantly hamper application and serial assessment of LVD in at-risk patients.…”
mentioning
confidence: 69%
“…to help come up with a decision about CRT implantation. 28,29 Unfortunately, to date we lack prospective randomized trials to show the value of such MPI dyssynchrony parameters on clinical decision making for CRT patient selection and CRT lead positioning. Thus future work will be tremendously important to clarify the significance of MPI-derived dyssynchrony in patients with and without electrical dyssynchrony and whether it is of value in guiding treatment pathways.…”
Section: See Related Article Pp 1227-1239mentioning
confidence: 99%